2002
DOI: 10.1021/ma010104+
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Blend Interface Type on Morphology in Cocontinuous Polymer Blends

Abstract: Three different categories of blend interfaces are examined systematically in order to isolate the role of the interface in the development of cocontinuous morphologies during melt mixing. They are Type I, compatible binary blends based on high-density polyethylene (HDPE)/styrene-ethylene-butylenestyrene (SEBS) and HDPE/styrene-ethylene-butylene (SEB); Type II, an incompatible binary system comprised of HDPE/polystyrene (PS); and Type III, compatible ternary systems comprised of HDPE/PS compatibilized by SEBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
132
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 32 publications
(90 reference statements)
11
132
1
Order By: Relevance
“…This highly stable thread behavior occurs as a result of the very low interfacial tension between EPDM and PP and can be explained directly from Tomotika theory [44] as outlined in other work [33,[45][46][47][48]. This result is also a support for the observation of highly stable fibers that will be discussed later in this paper.…”
Section: Interfacial Tension and Miscibility/immiscibilitysupporting
confidence: 77%
See 1 more Smart Citation
“…This highly stable thread behavior occurs as a result of the very low interfacial tension between EPDM and PP and can be explained directly from Tomotika theory [44] as outlined in other work [33,[45][46][47][48]. This result is also a support for the observation of highly stable fibers that will be discussed later in this paper.…”
Section: Interfacial Tension and Miscibility/immiscibilitysupporting
confidence: 77%
“…Both polymers are amorphous in nature and possess an interfacial tension of 0.6 mN/m. In that work it was shown that, because of the partial miscibility, the blend demonstrated significantly different morphological features as compared to that reported for fully immiscible blends of low interfacial tension by Li et al [33]. Marin et al found that these partially miscible blends exhibited very fine dispersed phase morphologies, artificially high percolation thresholds, and attained cocontinuity at higher than expected compositions of the minor phase.…”
Section: Introductionmentioning
confidence: 75%
“…Granular starches are compact particles, such as those observed in the PE2/TPS40 blends. Fiber-like particles observed in PE1/TPS40 blends could be responsible for a lower apparent percolation threshold in this system and, consequently, higher enzymatic degradation values (Li et al, 2005). Extent of enzymatic degradation of LDPE/TPS40 blends is very similar to that obtained by acid hydrolysis.…”
Section: Enzymatic Degradation Of Ldpe/tps40 Blendssupporting
confidence: 56%
“…Farhangi et al [120] pointed out that for gas separation, the membrane must have small enough porosity and pore size so as to increase the selectivity, and a thinner skin layer so as to improve gas permeation flux. The role of the interface on continuity development for PE/PS systems was investigated [121]. It was shown that the pore sizes in those systems could be controlled from 0.3 to 6.3 mm.…”
Section: Permeation Testmentioning
confidence: 99%